Implications of Glacial Melt-Related Processes on the Potential Primary Production of a Microphytobenthic Community in Potter Cove (Antarctica) - Hoffmann, Ralf; Al-Handal, Adil Yousif; Wulff, Angela; Deregibus, Dolores; Zacher, Katharina; Quartino, María Liliana; Wenzhöfer, Frank; Braeckman, Ulrike (Frontiers in Marine Science, 2019)
The Antarctic Peninsula experiences a fast retreat of glaciers, which correlates with an increased release of particles and related increased sedimentation and, thus, a decrease in the available photosynthetic active radiation (PAR, 400–700 nm) for benthic primary production. We investigated how changes in the general sedimentation and shading patterns affect the primary production by benthic microalgae, the microphytobenthos. In order to determine potential net primary production and respiration of the microphytobenthic community, sediment cores from locations exposed to different sedimentation rates and shading were exposed to PAR of 0–70 µmol photons m-2 s-1. Total oxygen fluxes and microphytobenthic diatom community structure, density, and biomass were determined. Our study revealed that the net primary production of the microphytobenthos decreased with increasing sedimentation and shading, while the microphytobenthic diatom density and composition remained similar. By comparing our experimental results with in situ measured PAR intensities, we furthermore assessed the microphytobenthic primary production as an important carbon source within Potter Cove’s benthic ecosystem. We propose that the microphytobenthic contribution to the total primary production may drop drastically due to Antarctic glacial retreat and correlated sedimentation and shading, with yet unknown consequences for the benthic heterotrophic community, its structure, and diversity.